Pengaruh Penggunaan Metode Role Playing Terhadap Sikap Peduli Sosial Pada Tema 4 Subtema 1 Pembelajaran 4 Pada Peserta Didik Kelas V B SD Negeri Nusukan Surakarta Tahun Pelajaran 2021/2022 - Khalila Aya Markatin; Oktiana Handini (Journal on Education, 2023)
The goal to be achieved in this research is to find out whether there is a role-playing learning method in cultivating a socially caring attitude towards students in class V B at SD Negeri Nusukan Surakarta in the 2021/2022 academic year. This research was conducted at SD Negeri Nusukan Surakarta, with a quantitative research paradigm. Data collection methods used are questionnaires and documentation. The data analysis technique used was an instrument trial, namely the t test in the form of a statistical data table which conclusions would then be drawn. Based on the results of the research and discussion, it can be concluded that there is a significant influence on the Social Care Attitude of students in class V B of SD Negeri Nusukan, Surakarta Academic Year 2021/2022 from activities before treatment and after treatment is applied. The social caring attitude of class V B students is proven in the pre-test results, namely 102.5 and the post-test results, namely 108.03. Comparison between pre-test and post-test has different results. In calculating the statistical data analysis value of the Paired Samples Test about the Effect of the Role-Playing Method, a significance value of 0.000 is obtained where the sig value of 0.000 <0.05 means Ho is rejected and Ha is accepted. Based on the table above t_count is -4.522 the t_count value can be compared with t_table dk = (N-1) so (28-1) = 27 at the 5% significance level, namely 2.052. Based on these results, it can be concluded that the application of the role-playing method effected on social care attitudes